Negotiating universalism in India and Latin America: Fiscal decentralization, subnational politics and social outcomes. Issue 2 (15th March 2019) - Mejia Acosta, Andres; Tillin, Louise
ABSTRACT: This is the introductory paper for a special issue which focuses on an exploration of how vertical inter-governmental political and fiscal bargains and horizontal variation in political, social and economic conditions across regions contribute to or undermine the provision of inclusive and sustainable social policies at the subnational level in Latin America and India. The papers incorporate both federal, as well as decentralized unitary states, pointing to common political tensions across unitary and federal settings despite the typically greater institutionalization of regional autonomy in federal countries. Jointly, the papers examine the territorial dimension of universalism and explore, in greater and empirical detail, the causal links between fiscal transfers, social policies and outcomes, highlighting the political dynamics that shape fiscal decentralization reforms and the welfare state. This introductory essay reviews existing scholarship, and highlights the contribution of the special issue to understanding these issues beyond OECD contexts.